Chilling of Steindachneridionparahybae (siluriformes: pimelodidae) embryos - Lopes, Taís da Silva; Sanches, Eduardo Antônio [UNESP]; Okawara, Renan Yoshiharu; Romagosa, Elizabeth (Elsevier B. V., 2015)
The objective of this study was to assess the viability of Steindachneridion parahybae embryos after chilling using different cryoprotectant solutions, stages of embryonic development, chilling curves, and storage periods at temperatures between -10 °C and 0 °C. Three experimental tests were conducted, and the following aspects were evaluated: (1) the toxicity of six cryoprotectant solutions (10% methanol, ethylene glycol, or DMSO combined with 0.5-M sucrose or lactose); (2) viability of embryos submitted to cooling with two cryoprotectant solutions (10% or 20% methanol combined with 10-M sucrose) at three different stages of development (closure of blastoporus, appearance of the optic vesicle and the moment when the tail began to straighten out), and two chilling periods (6 and 12 hours); (3) viability of embryos submitted to cooling with three chilling curves (directly to the freezer without a curve, 0.5 °C/min and 1.0 °C/min) and two chilling periods (6 and 12 hours). After the tests, it was concluded that the protocol which presented the most positive results after chilling, with a hatching rate of 63.50 ± 9.98% of the embryos and 12.32 ± 3.85% normal hatched larvae, was the one with embryos at the free-tail stage, the cryoprotectant solution with 10% methanol and 10-M sucrose, a chilling curve of 0.5 °C/min, stored for a maximum of 6 hours at subzero temperatures (temperature ranging between -5.05 °C and -7.83 °C).
Keywords: Cryopreservation; Cryoprotectant solution; Endangered fish; Neotropical catfish; Ontogenetic development; Preservation of embryo